INVESTIGATION THE ASSOCIATION BETWEEN MTHFR GENE POLYMORPHISM AND HOMOCYSTEINE IN IRANIAN PREGNANT WOMEN - Sonbolestan, Elham Sadat; Sazegar, Hossein; Zia-jahromi, Noosha; Farsani, Farzaneh Mohamadi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This study was aimed to investigate the association between polymorphisms in MTHFR gene and Vitamin B12-dependent homocysteine metabolism. Methods: Hyperhomocysteinemia has been implicated as a risk factor for complications in pregnancy including abortion, preeclampsia, and placental abruption. Several epidemiological studies have investigated the associations of MTHFR C677T polymorphism with hypertension or hypertension in pregnancy. However, the results were controversial. Numbers of 100 samples from healthy pregnant women as control criteria and 100 samples from fertile women have been collected. Due to research on MTHFR polymorphism, special primers have been designed. The research on MTHFR polymorphism has been done by restriction fragment length polymorphism assay. Results: The results demonstrated 9.26% have been registered for heterozygous individuals and the homocysteine level of homozygous individuals was 41.18% (higher than the normal level). The results showed a significant difference in the homocysteine levels of homozygous individuals and the homocysteine levels of healthy individuals (p=0.004). Furthermore, there was no significant difference in the homocysteine levels of heterozygous individuals and the homocysteine levels of healthy individuals (p=0.34). Similarly, a significant difference in the B12 levels in blood of homozygous individuals and the homocysteine levels of healthy individuals have been showed (p=0.00). Conclusion: The mutation of gene MTHFR C677T causes an increase of the homocysteine level, decrease of the level of folic acid and B12 vitamin in heterozygous individuals but a relationship among homocysteine level, the level of folic acid and B12 vitamin not found.